2016
DOI: 10.1016/j.bbi.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine-2,3-dioxygenase mediates neurobehavioral alterations induced by an intracerebroventricular injection of amyloid-β1-42 peptide in mice

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder that is characterized by a progressive cognitive decline along with various neuropsychiatric symptoms, including depression and anxiety. Increasing evidence has been proposed the activation of the tryptophan-degrading indoleamine-2,3-dyoxigenase (IDO), the rate-limiting enzyme of kynurerine pathway (KP), as a pathogenic factor of amyloid-beta (Aβ)-related inflammation in AD. In the current study, the effects of an intracerebroventricular (i.c.v.) injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…Our results also showed that 1-MT-treated BDL rats had restored memory performance and learned faster than non-treated rats, suggesting IDO regulation may be related to the memory deficits induced by BDL surgery. Corroborating our results, 1-MT treatment can ameliorate the memory deficit induced by amyloid-β1-42 peptide in mice [ 54 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results also showed that 1-MT-treated BDL rats had restored memory performance and learned faster than non-treated rats, suggesting IDO regulation may be related to the memory deficits induced by BDL surgery. Corroborating our results, 1-MT treatment can ameliorate the memory deficit induced by amyloid-β1-42 peptide in mice [ 54 ].…”
Section: Discussionsupporting
confidence: 78%
“…Some earlier researches confirmed our results: BDL rats spent less time in the open arms and more time in the closed arms of the maze as compared to the control animals [ 52 , 53 ]. Furthermore, Souza et al’s study had shown that 1-MT may process anti-anxiety-like action in neurodegenerative disorder [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the neuroprotective mechanism of lupeol in the Aβ-mouse model of AD, which suggested that lupeol suppressed the elevated oxidative stress, neuroinflammation, and memory and cognitive dysfunctions. The pathogenesis of AD occurred due to the accumulation of toxic Aβ-peptide in the central nervous system, causing synaptic dysfunction, neuronal cell death, and memory and cognitive impairments [ 42 , 43 ]. The amyloid precursor protein (APP) can be cleaved by the beta-amyloid cleaving enzyme (BACE-1), which accelerates the production of Aβ-peptide in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…KP is unbalanced in some neurodegenerative disorders and, as a result, Trp catabolism leads to neurotoxic metabolites such as 3-hydroxykunurenine. IDO1 is essential for this pathway, and its activation has been linked with A β -related inflammation in AD [ 49 ], making it the focus of various researches on neurodegenerative diseases treatment [ 50 51 ]. Lu et al have identified a novel structure endowed with double activity on BuChE and IDO1 [ 52 ].…”
Section: Target Combinations In Mtdl Design Strategy For Admentioning
confidence: 99%